Edukasi Etika Batuk Sebagai Upaya Pencegahan TB Paru Sejak Dini Pada Siswa SD Negeri Mattoangin 1 Kota Makassar - Pakadang, Sesilia Rante (Jurnal Pengabdian Kefarmasian, 2024)
Education On Cough Ethics as an Early Prevention of Pulmonary Tb for Students of Mattoangin 1 State Primary School, Makassar CityBackground: Pulmonary tuberculosis (pulmonary TB) is ranked 13th and the second infectious disease after Covid-19 as the main cause of death in the world. Coughing is a common symptom of pulmonary TB and effective coughing is highly recommended for pulmonary TB sufferers to reduce the burden of shortness of breath and expel mucus properly. However, cough etiquette is very important to prevent transmission of pulmonary TB infection.  The aim of the activity is to provide education and training in implementing cough etiquette Activity Method.  Education and training. The target audience is 30 students and teachers at SD Negeri Mattoangin 1 Makassar City. Evaluation of activities in the form of pre and post educational questionnaires. Training activities are evaluated based on students' skills in implementing cough etiquette.  Activity Results. The increase in participants' knowledge after education was 60% and students were able to carry out cough etiquette correctly.     Conclusion. Education has increased knowledge by 60% and participants have demonstrated skills in implementing correct cough etiquette. Latar Belakang. Tuberkulosis paru (TB paru) menduduki peringkat ke 13 dan penyakit menular kedua setelah Covid-19 sebagai penyebab utama kematian di dunia. Batuk merupakan gejala umum dari TB paru dan batuk efektif sangat disarankan pada penderita TB paru untuk mengurangi beban sesak napas dan mengeluarkan lendir dengan baik. Namun etika batuk sangat penting dilakukan untuk mencegah penularan infeksi TB paru.   Tujuan Kegiatan memberikan edukasi dan pelatihan melaksanakan etika batuk Metode Kegiatan. Edukasi dan pelatihan. Khalayak sasaran adalah siswa dan guru SD Negeri Mattoangin 1 Kota Makassar berjumlah 30 orang. Evaluasi kegiatan berupa kuesioner pre dan post edukasi. Kegiatan pelatihan dievaluasi berdasarkan keterampilan siswa melaksanakan etika batuk. Hasil Kegiatan. Peningkatan pengetahuan peserta setelah edukasi sebesar 60% dan siswa telah mampu melaksanakan etika batuk dengan benar.  Kesimpulan. Edukasi telah meningkatkan pengetahuan sebesar 60% dan peserta telah menunjukkan keterampilan melaksanakan etika batuk yang benar.